The Effectiveness of the Roni App in Enhancing the Resilience of Tuberculosis Patients - Permana, Roni; Afrizal; Yunus, Faisal; Bachtiar, Adang (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Tuberculosis (TB) remains a significant global health burden, requiring not only adherence to treatment regimens but also robust psychological resilience for successful recovery. This study evaluated the efficacy of the Roni application, a novel technology-based intervention designed to enhance resilience among TB patients. Employing a quasi-experimental design, 60 TB patients were randomized into an intervention group (n=30) and a control group (n=30). The intervention group utilized the Roni application for one month, while Patients in the control group received standard care. Resilience was assessed at baseline and post-intervention using the Brief Resilience Coping Scale (BRCS). Results demonstrated a statistically significant improvement in resilience scores among participants in the intervention group compared to the control group (p < 0.05). By providing tailored educational resources, motivational support, and opportunities for emotional processing, the Roni application appears to enhance resilience in TB patients effectively. These findings align with theoretical frameworks of stress adaptation and self-efficacy. This study contributes to the growing body of evidence supporting the potential of technology-based interventions to address the psychosocial needs of TB patients and improve treatment outcomes. Future research should investigate the long-term sustainability of these effects and explore the generalizability of this intervention across diverse populations.